Python for beginners : a complete beginner's guide to learning Python quickly / Daniel O'Reilly. - O'Reilly, Daniel (Writer on Python) (publisher not identified, 2021)
Python is top on the list of the most diverse, flexible, and easy to learn programming languages. It's used in almost every industry, for all types of software. If you learn Python, you'll be able to find a job almost everywhere and especially in the emerging field of data science.